Aplikasi Pemesanan Tiket Travel Berbasis Android Menggunakan Metode Waterfall - Maulana Misbah, Baharudin; Murdiani, Deni (CV RIFAINSTITUT, 2021)
Sadam Jaya Travel is a company engaged in transportation, namely travel between provinces in Java Island. So far the service of purchasing travel tickets by prospective passengers is still conventional, which is only limited to booking services via SMS or phone directly to the driver or kernet. This condition raises the problem of often forgetting the driver to pick up prospective support so that there are often complaints by prospective passengers. Therefore, a system is needed that can manage prospective passengers who book tickets to be recorded. In this research I intend to design the Sadam Jaya Travel application in the hope that the problems that have arisen can be resolved properly. The application development methodology that the author uses is a waterfall process with stages of analysis, design, implementation, testing, maintenance. The results of this study resulted in the Sadam Jaya Travel application using Android Studio with Kotlin and Firebase languages as a database and can be implemented properly using the Waterfall method and resulting in 100% accepted testing.